Marketing Strategies For Eco-Tourism in Air Terjun Gunung Janggot, Central Lombok Regency: A Focus on Sustainability and Community Engagement - Rumba; Baiq Ayu Sartika (Politeknik Pariwisata Makassar, 2024)
The Central Lombok area is renowned for its natural tourist destinations, such as beaches and waterfalls. However, many natural attractions, like the Air Terjun Gunung Janggot in Aik Berik Village, North Batukliang District, remain relatively unknown to tourists. This study investigates marketing strategies for eco-tourism at Air Terjun Janggot, emphasizing sustainability and community engagement. The region has significant potential to develop into a sustainable and environmentally friendly tourism destination. The purpose of this research is to determine the promotional strategies used for Air Terjun Gunung Janggot. Data collection methods include qualitative approaches such as observation, documentation, and interviews. The findings reveal that the promotional strategy employed primarily involves the POSE strategy, focusing on Owned Media as the main tool for digital promotion. The research also evaluates various other marketing methodologies, including the utilization of social media, narrative-based promotion, and community-centered marketing. Local community involvement is highlighted as a critical component, considering both their role in the operation of the destination and their potential benefits from tourism activities. A participatory and inclusive approach is advocated, which is anticipated to enhance local economic prosperity while safeguarding the natural environment of Air Terjun Janggot. The study provides actionable recommendations for destination managers and relevant stakeholders to implement effective and sustainable marketing strategies.